Evaluation of mixing performance and validation of CFD simulations in baffled anaerobic digesters using radiotracer technique. (February 2023) - Goswami, Sunil; Kshirsagar, V.S.; Aswini, V.; Sharma, V.K.; Samantray, J.S.; Gupta, Raghvendra; Pawar, P.M.; Pant, H.J.
Abstract: The anaerobic digesters find usage in treating the huge amount of waste such as trash, garbage, human waste and animal waste. The sustained performance of an anaerobic digester depends on the flow pattern and mixing behaviour in the digester. A cylindrical digester tank with vertical baffles can provide flow behaviour approaching that of a plug flow reactor. However, the presence of dead zones and recirculating regions cause non-ideal flow in the digester. In this work, the mixing behaviour in two scaled-down models of baffled digester tanks is characterized by measurement of residence time distribution (RTD) using a radioactive tracer. While the first design has three vertical baffles, the second design include horizontal static flaps on the baffles. The flow behaviour in the digester is also simulated using computational fluid dynamics (CFD) and RTD is obtained computationally. The comparison of RTD curves obtained from CFD simulations with those obtained from radiotracer experiments show good agreement between them. There appear to be only minor difference in the flow behaviour and the RTD curves in the two digester designs. Using the RTD curve data, two commonly used RTD models, tank-in-series and dispersion models, have been fitted and both models are able to predict the RTD in the digester qualitatively. Highlights: Residence time distribution in a laboratory scale digester is investigated. Details of the hydrodynamics is investigated using CFD. CFD modeling and radiotracer methodologies are used. RTD data fitted with the tank-in-series and dispersion models.